2021
DOI: 10.1111/ajt.16509
|View full text |Cite
|
Sign up to set email alerts
|

Early liver transplantation after COVID-19 infection: The first report

Abstract: COVID‐19 (coronavirus disease 2019) has impacted solid organ transplantation (SOT) in many ways. Transplant centers have initiated SOT despite the COVID‐19 pandemic. Although it is suggested to wait for 4 weeks after COVID‐19 infection, there are no data to support or refute the timing of liver transplant after COVID‐19 infection. Here we describe the course and outcomes of COVID‐19‐infected candidates and healthy living liver donors who underwent transplantation. A total of 38 candidates and 33 potential livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
0
41
0
2
Order By: Relevance
“…This complication remains a rare complication and even fewer cases of transplantation after COVID-19 infection have been reported. 28 As more patients recover from COVID-19, it is possible that they will have other viral sequelae, or sequelae from medications administered during treatment, requiring further work-up as described here. It has been widely reported that patients with underlying liver disease represent a higher risk of severe COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…This complication remains a rare complication and even fewer cases of transplantation after COVID-19 infection have been reported. 28 As more patients recover from COVID-19, it is possible that they will have other viral sequelae, or sequelae from medications administered during treatment, requiring further work-up as described here. It has been widely reported that patients with underlying liver disease represent a higher risk of severe COVID-19 illness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, SARS-CoV-2 can worsen liver disease, and LT cannot be delayed due to increased waitlist mortality risk [8,9]. Therefore, transplant centres have initiated SOTs globally [9,10]. Given that the effects of COVID-19 on liver graft injury in LT recipients are unclear, it is crucial to understand the clinical course, management, and outcomes of COVID-19 in these patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the presence of comorbidities and chronic immunosuppression may increase the risk of severe COVID-19 among SOT recipients [ 6 , 7 ]. Further, SARS-CoV-2 can worsen liver disease, and LT cannot be delayed due to increased waitlist mortality risk [ 8 , 9 ]. Therefore, transplant centres have initiated SOTs globally [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is the first unique report of COVID-19 masquerading as an AIH flare from India. COVID-19 can lead to ACLF and is associated with poor outcomes 3 , 4 . The abnormalities in liver function tests in COVID-19 could be due to virus-related cytopathic effects or nonviral causes such as cytokine storm, hypoxia, and hepatotoxic medications 1 , 5 .…”
mentioning
confidence: 99%